Low-Dose Methotrexate (LD-MTX) in Rheumatology Practice - A Most Widely Misunderstood Drug - N. Malaviya, Anand (Current Rheumatology Reviews, 2016)
Methotrexate (MTX) was synthesised as a folate antagonist for use in treating childhood leukaemia in 1940s. Gubner and colleagues in 1953 used several log-order lower doses of MTX that mimicked the anti-inflammatory properties of cortisone. They used it successfully in treating rheumatoid arthritis (RA). Their work was however overlooked because the Nobel Prize winning drug cortisone held sway in those days. With increasing awareness of the adverse effects of cortisone, interest was rekindled in discovering ‘steroid-sparing’ drugs. Hoffmeister and Willkens used low-dose MTX (LD-MTX) in treating RA patients in 1960s with impressive results. Pivotal trials in 1984-5 established the efficacy and safety of LD-MTX in treating RA that gained FDA approval in 1988. LD-MTX at doses <25-30 mg weekly as mini-pulses, is presently the standard-of-care for the treatment of RA. Its toxicities and adverse effects are rarely if ever life-threatening. This is in contrast to the high-dose methotrexate (HD-MTX) for treating malignancies at doses that are several log-orders higher and usually cause serious toxicities. While LD-MTX acts mainly as an anti-inflammatory drug by increasing tissue adenosine levels besides other mechanisms, HD-MTX has anti-proliferative cytotoxic action with different toxicity profile and adverse effects. In practical terms LD-MTX and HD-MTX are 2 different therapeutic agents. However, in developing countries like India the stigma attached to MTX as a cytotoxic ‘cancer drug’ still persists and most non-rheumatologists fear its use in RA. This review aims to allay such anxiety attached to LD-MTX so that they start using it in appropriate doses for treating RA.
Keywords: Methotrexate